Two Hydroxypyruvate Reductases Encoded by OsHPR1 and OsHPR2 are Involved in Photorespiratory Metabolism in Rice. Issue 2 (8th January 2014) - Ye, Nenghui; Yang, Guozhen; Chen, Yan; Zhang, Chan; Zhang, Jianhua; Peng, Xinxiang
Abstract Mutations in the photorespiration pathway display a lethal phenotype in atmospheric air, which can be fully recovered by elevated CO2. An exception is that mutants of peroxisomal hydroxypyruvate reductase (HPR1) do not have this phenotype, indicating the presence of cytosolic bypass in the photorespiration pathway. In this study, we constructed overexpression of the OsHPR1 gene and RNA interference plants of OsHPR1 and OsHPR2 genes in rice (Oryza sativa L. cv. Zhonghua 11). Results from reverse transcription‐polymerase chain reaction (RT‐PCR), Western blot, and enzyme assays showed that HPR1 activity changed significantly in corresponding transgenic lines without any effect on HPR2 activity, which is the same for HPR2. However, metabolite analysis and the serine glyoxylate aminotransferase (SGAT) activity assay showed that the metabolite flux of photorespiration was disturbed in RNAi lines of both HPR genes. Furthermore, HPR1 and HPR2 proteins were located to the peroxisome and cytosol, respectively, by transient expression experiment. Double mutant hpr1 × hpr2 was generated by crossing individual mutant of hpr1 and hpr2. The phenotypes of all transgenic lines were determined in ambient air and CO2‐elevated air. The phenotype typical of photorespiration mutants was observed only where activity of both HPR1 and HPR2 were downregulated in the same line. These findings demonstrate that two hydroxypyruvate reductases encoded by OsHPR1 and OsHPR2 are involved in photorespiratory metabolism in rice.